C‐reactive protein levels in hereditary angioedema. (July 2014) - Hofman, Z. L. M.; Relan, A.; Hack, C. E.
Summary Hereditary angioedema (HAE) patients experience recurrent episodes of angioedema attacks that can be painful, disfiguring and even life‐threatening. The disorder results from a mutation in the gene that controls the synthesis of C1‐inhibitor (C1INH). C1INH is a major regulator of activation of the contact system. It is often assumed that attacks results from uncontrolled local activation of the contact system with subsequent formation of bradykinin. To evaluate the involvement of inflammatory reactions in HAE, we analysed C‐reactive protein (CRP) levels. HAE patients included in a clinical database of recombinant human C1‐inhibitor (rhC1INH) studies were evaluated. For the current study we analysed CRP levels when patients were asymptomatic, during a clinical attack and in a follow‐up period, and correlated these with the clinical manifestations of the attack. Data from 68 HAE patients were analysed and included CRP levels on 273 occasions. While asymptomatic, 20% of the patients analysed had increased CRP. At the onset of the attack (P = 0·049) and during the next 24 h CRP rose significantly (P = 0·002) in patients with an abdominal location, and post‐attack levels were significantly higher in these patients than in patients with attacks at other locations (P = 0·034). In conclusion, CRP levels are elevated in a substantial proportion of asymptomatic HAE patients. Levels of CRP increase significantly during an abdominal attack. These data suggest low‐grade systemic inflammatory reactions in HAE patients as well as a triggering event for attacks that starts prior to symptom onset.